OPTIMALISASI PENGEMBANGAN KEMASAN PRODUK UMKM KEMPLANG IKAN NAJWA DI DESA TALANG NANGKA KECAMATAN LEMBAK KABUPATEN MUARA ENIM - Rasid Siddik; Ririn Nurmila Sari; Putri Afifah Khayrani; Lidia Heni Sulistiani; Meilin Veronica; Muhammad Bahrul Ulum; RM Rum Hendarmin (Aptekmas Jurnal Pengabdian pada Masyarakat, 2023)
This devotional journal discusses efforts to improve the development of MSME product packaging "Kemplang Ikan Najwa" in Talang Nangka Village, Lembak District, Muara Enim Regency. MSMEs have an important role in the local and national economy, but often face obstacles in competing with large products. Therefore, packaging optimization is an important strategy in increasing the competitiveness of MSME products. This service involves several steps. First, a market survey is conducted to understand consumer preferences and needs. Competitor analysis was also carried out to identify the advantages and disadvantages of similar product packaging on the market. Furthermore, a consultation was carried out with the owner of the UMKM "Kemplang Ikan Najwa" to understand the vision and value of their product. Based on the results of analysis and consultation, packaging design improvements were made. Packaging design is improved to be more attractive and reflect product identity. Factors such as color, logo, product information and functional features are integrated into the new packaging design. It is hoped that the results of this optimal packaging development will increase consumer interest in MSME products "Kemplang Ikan Najwa". Attractive and functional packaging can help products be more easily recognized in the market, increase visual appeal, and drive increased selling points. In conclusion, this dedication succeeded in optimizing the development of MSME product packaging "Kemplang Ikan Najwa" in Talang Nangka Village. The use of packaging designs that are more attractive and in accordance with product identity is expected to help MSMEs achieve greater success in marketing their products.